Pertentangan Hati Nurani dan Etika Pelayanan - Aprianus Simanungkalit (Sekolah Tinggi Alkitab Penyebaran Injil Majalengka, 2021)
Everyone in life will always be faced with various problems. There are light problems and there are difficult problems to deal with. There are people who are so relaxed every time they face the problems that exist, but not a few people who are so panicked about life's problems, some even end their lives. When faced with this problem, the person is required to make the right decision. Making an ethical decision remains a struggle for everyone because making ethical decisions is very difficult, it requires peace of mind and mind. In this discussion, I will discuss the understanding of ethical decisions based on conscience. I think conscience will try to help someone in carrying out an ethical action so that the decision taken is the right decision.Setiap orang hidup akan selalu diperhadapakan dengan beragam persoalan. Ada persoalan yang ringan ada juga persoalan yang sulit untuk dihadapi. Ada orang yang begitu santai setiap menghadapi persoalan yang ada, tetapi tidak sedikit juga orang yang begitu panik menghadapi persoalan hidup bahkan ada yang sampai mengakhiri hidupnya. Saat bertemu dengan persoalan itu, orang tersebut dituntut untuk mengambil sebuah keputusan yang tepat. Mengambil sebuah keputusan etis tetap menjadi pergumulan setiap orang, kare¬na mengambil keputusan etis sangat sulit, dibutuhkan ketenangan hati dan pikiran. Dalam pembahasan ini, saya akan membahas tentang pemahaman keputusan etis berdasarkan hati nurani. Menurut saya hati nurani sampai saat ini akan berusaha membantu seseorang dalam melakukan sebuah tindakan etis, sehingga keputusan yang diambil adalah sesuatu keputusan yang benar.